2002
DOI: 10.1152/jn.00938.2000
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Potentiation in Direct Perforant Path Projections to the Hippocampal CA3 Region In Vivo

Abstract: Derrick. Long-term potentiation in direct perforant path projections to the hippocampal CA3 region in vivo. J Neurophysiol 87: 669 -678, 2002; 10.1152/jn.00938.2000. The perforant path constitutes the primary projection system relaying information from the neocortex to the hippocampal formation. Long-term synaptic potentiation (LTP) in the perforant path projections to the dentate gyrus is well characterized. However, surprisingly few studies have addressed the mechanisms underlying LTP induction in the direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 39 publications
(64 reference statements)
7
66
1
Order By: Relevance
“…Different afferent systems of the hippocampus can display distinct mechanisms of LTP induction (Harris and Cotman, 1986;Derrick and Martinez, 1989;Bramham et al, 1991;Grover and Teyler, 1995;Do et al, 2002). The present data extend these findings to indicate that LTP displaying distinct properties, such as enhanced longevity, can be induced in distinct behavioral states even within a single synaptic population.…”
Section: Discussionsupporting
confidence: 75%
“…Different afferent systems of the hippocampus can display distinct mechanisms of LTP induction (Harris and Cotman, 1986;Derrick and Martinez, 1989;Bramham et al, 1991;Grover and Teyler, 1995;Do et al, 2002). The present data extend these findings to indicate that LTP displaying distinct properties, such as enhanced longevity, can be induced in distinct behavioral states even within a single synaptic population.…”
Section: Discussionsupporting
confidence: 75%
“…Homosynaptic LTP-heterosynaptic LTDs have been observed previously in the CA1 (Lynch et al, 1977;Dunwiddie and Lynch, 1978), CA3 (Bradler and Barrioneuvo, 1989;Martinez et al, 2002), and dentate gyrus (Levy and Steward, 1979;Abraham and Goddard, 1983) regions of the hippocampus, in the cortex (Tsumoto and Suda, 1979;Hirsch et al, 1992), and in cultured neuromuscular junctions (Lo and Poo, 1991). In addition, homosynaptic LTP at the T-S synapse is NMDAR independent, a trait that is also observed in the LTP found in various regions of the mammalian brain (Nicoll and Malenka, 1995;Salin et al, 1996;Do et al, 2002a). One surprising feature about the T-S synapse is that although homosynaptic LTP is NMDAR independent, heterosynaptic LTD required NMDAR activity, the reverse of what is typically observed (for review, see Linden and Connor 1995).…”
Section: Homosynaptic Ltp-heterosynaptic Ltd At the T-s Synapsesupporting
confidence: 54%
“…Studies have demonstrated that direct projection from the perforant path to CA3 mediates distinct and essential functions (Marr, 1971;Morris and Mcnaughton, 1987), and plasticity induced in the direct perforant path-CA3 projection during learning serves subsequently as the primary input for memory (Treves and Rolls, 1994). Associative LTP can be induced in the perforant path-CA3 pathway, and this form of LTP plays an important role in the hippocampal information processing (Berger and Yeckel, 1991;Do et al, 2002). This summing-up evidence directed us to the design of the LTP study as shown in Figure 1 A.…”
Section: Discussionmentioning
confidence: 99%